2001
DOI: 10.1080/080352501317061585
|View full text |Cite
|
Sign up to set email alerts
|

Acute postnatal increase of extracellular antioxidant defence of neonates: the role of iron metabolism

Abstract: These results suggest that extracellular antioxidant capacity (both chain-breaking and heme-specific antioxidant activities) increases shortly after birth. Lower iron and higher ferritin levels could also be responsible for this phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
5
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…In our previous work we have shown that acute and abrupt changes of iron homeostasis (i.e., dramatic drop of serum iron and the dynamic increase of serum ferritin and antioxidant capacity) occur within the first postnatal day [14]. Similar tendencies were also demonstrated in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our previous work we have shown that acute and abrupt changes of iron homeostasis (i.e., dramatic drop of serum iron and the dynamic increase of serum ferritin and antioxidant capacity) occur within the first postnatal day [14]. Similar tendencies were also demonstrated in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…RBC and iron parameters in CB and PN samples were in the same range as those reported in other studies, including our own previous work [14,15]. RBC, Hgb, Ht, MCHC, and ferritin levels in PN samples were higher than in corresponding CB samples, while iron levels and transferrin saturation were lower (see Table 1).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The contribution by the antioxidant substances to the total antioxidant defence system may therefore be particularly important in the immediate postnatal period. High serum levels of vitamin C and uric acid are present at birth and the rapid decline of vitamin C and thereafter uric acid appears to be compensated for by the simultaneous increase in serum bilirubin (4)(5)(6) In this issue of Acta Paediatrica, Szabo et al present the changes over the rst 48 h in the serum-preventive and chain-breaking antioxidants in the healthy term baby (7). They show that there is a rapid increase in both the iron-binding capacity and the total chain-breaking antioxidant capacity, and suggest that these changes contribute to the successful adaptation the baby makes to the relatively hyperoxic environment of extra-uterine life (2).…”
mentioning
confidence: 99%
“…This NPBI, because of the high vitamin C and low ceruloplasmin levels at birth, is in the highly active reduced form and may induce oxidative damage (see recent review (12)). Instead of performing the complex and often dif cult tests to directly measure NPBI and assess iron-binding and iron-oxidizing capacity of plasma, Szabo et al (7) simply measured the serum iron and transferrin concentrations and calculated the latent iron-binding capacity. They showed that, although the transferrin levels were stable, the dramatic fall in serum iron levels resulted in a 60% increase in the serum iron-binding capacity.…”
mentioning
confidence: 99%